2019
DOI: 10.1016/j.arcontrol.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Bibliographical review on cyber attacks from a control oriented perspective

Abstract: This paper presents a bibliographical review of definitions, classifications and applications concerning cyber attacks in networked control systems (NCSs) and cyber-physical systems (CPSs). This review tackles the topic from a control-oriented perspective, which is complementary to information or communication ones. After motivating the importance of developing new methods for attack detection and secure control, this review presents security objectives, attack modeling, and a characterization of considered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 262 publications
(319 reference statements)
0
60
0
Order By: Relevance
“…The former approach relies on data encryption techniques to protect critical sensor measurements, while the latter approach depends on secure anomaly identification methods to detect altered measurements. For a complete review of the effect of deception attacks on a CPS, see notable works in [4,42] for a review.…”
Section: Resilient Control Strategiesmentioning
confidence: 99%
“…The former approach relies on data encryption techniques to protect critical sensor measurements, while the latter approach depends on secure anomaly identification methods to detect altered measurements. For a complete review of the effect of deception attacks on a CPS, see notable works in [4,42] for a review.…”
Section: Resilient Control Strategiesmentioning
confidence: 99%
“…As an expansion of the study proposed in [ 19 ], the contributions of our study are as follows: When considering the flight as a part of a cyber physical system (CPS), many concerns that are related to the cybersecurity on the system have been raised, according to Sanchez et al in [ 20 ]. We proposed a series of analyses to extract an essential set of features from raw log-level flight data and validated that the set of features represents a distinct pattern between safe states and faulty states.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CPS attacks are difficult to trace, classify or identify the original threat, which may move or spread, and target multiple components of the system. For this reason, research on cyber attacks and secure control has found increasing interest [3].…”
Section: Introductionmentioning
confidence: 99%
“…Then, it is presented the mathematical model for different adversary models such as zero-dynamics attack, covert attack, false data injection attack and replay attack. In addition, Sanchez et al [3] provides a detailed bibliographic review of cyber-physical attacks given illustrative examples.…”
Section: Introductionmentioning
confidence: 99%